The potency of obtaining electrical energy from tofu industry liquid waste using salt bridge microbial fuel cell method - Agustin Hermayanti; Irwan Nugraha (Jurnal Sains Dasar, 2014)
Research on the acquisition of electric energy from waste water industry has been known using the so called salt bridge microbial fuel cell (SBMFC) method. MFC system (microbial fuel cell) is applied to tofu liquid waste management industry which generates two benefits that is reducing contamination of organic material and producing electricity. This study focused on the dual-chamber MFC system that comes as a salt bridge proton exchanger. Variation of the concentration of KMnO4 as an electrolyte solution is done to observe the effects on the acquisition of electrical energy. Changes in pH, COD, and BOD were also conducted to determine the effectiveness of the MFC in degrading wastewater of tofu. The results obtained in the form of electrical energy with a maximum power density of 11,941 mW/cm2 at concentration of 0.10 M. The pH value increase of KMnO4 occurred from 3.5 to 4.0 at concentration of 0.05 M KMnO4. Meanwhile the greatest decreases in COD values are 42.86% and 71.27%, respectively, at KMnO4 concentration of 0.10 M.   Key words: microbial fuel cell, dual-chamber, power density, electrical energy